Work-related stress among the university librarians of Sri Lanka - Wijetunge, Pradeepa (My University, 2012)
Sri Lankan university sector is changing rapidly as a result of educational reforms and the government's emphasis on a knowledge economy. As a consequence, the work environments of the university librarians are also changing. Although this environment can serve as a factor for increased work-related stress of the Librarians there is no evidence of any empirical studies related to stress of Sri Lankan University Librarians. This study was carried out with the objective of understanding the trend of stress among the University Librarians and to fill a void in the literature. This study was limited only to the University Librarians who are the Heads of the Libraries but not the other librarians below the rank of University Librarians. To suit the Sri Lankan needs a 95 item instrument which measured the stress level under employment, professional, administrative and health was designed based upon CAUT Survey (Catano 2011). Total Stress levels vary from Librarian to Librarian but five could be grouped into Medium Stress category with two in the High Stress category. Of the four domain surveyed, Physical Domain proved to be the least stressful domain while the Administrative Domain proved to be the highest stressful. Based on the previous studies researchers have discovered that performance improved with increased stress to an optimal point. Studies have proved resilient people found a stressful event intriguing and challenging. Considering these findings it was recommended that no initiative should be taken to reduce the current stress levels of the Sri Lankan University Librarians so that their stress factors are considered as a challenge and transformed into positive outcomes.